Find the general solution of each of the following
1) y''+y=Tanx
"We \\space have \\space (D^2 \\space + \\space 1)y \\space = \\space tanx \\space \\\\\nA.E. \\space is \\space m^2 \\space + \\space 1 \\space = \\space 0 \\space \\\\\ni.e., \\space m^2 \\space = \\space \u2013 \\space 1\\\\\n \\space i.e., \\space m \\space = \\space \u00b1 \\space i \\space \\\\\nC.F. \\space is \\space C.F. \\space = \\space y_c \\space = \\space \\space C_1cos \\space x \\space + \\space \\space C_2sinx \\space \\\\\n\u2234 \\space y \\space = \\space A \\space cos \\space x \\space + \\space B \\space sinx \\space ...(1) \\space \\\\\nbe \\space the \\space complete \\space solution \\space of \\space the \\space given \\space equation \\space where \\space A \\space and \\space B \\\\\n \\space are \\space to \\space be \\space found \\space \\\\\nWe \\space have \\space y_1 \\space = \\space cos \\space x \\space and \\space y_2 \\space = \\space sin \\space x \\space \\\\\ny\u2032_1 \\space = \\space \u2013 \\space sinx \\space y\u2032_2 \\space = \\space cos \\space x\\\\\n \\space W \\space = \\space y_1y'_2 \\space - \\space y_2y'_1 \\space = \\space cos \\space x \\space . \\space cos \\space x \\space + \\space sin \\space x \\space . \\space sin \\space x \\space = \\space cos2x \\space + \\space sin2x \\space = \\space 1 \\space \\\\\nalso \\space \\phi \\space (x)= \\space tan \\space x \\space \\\\\nA' \\space = \\space \\frac{-y_2 \\space \\space \\space \\phi \\space (x)}{W} \\space \\\\\n \\space \\space \\space \\space \\space = \\space \\frac{-sin \\space x \\space \\space \\space tan \\space x \\space }{1} \\space \\\\\nA' \\space = \\space \\frac{-sin \\space ^2 \\space x}{cos \\space x} \\space \\\\\nA \\space = \\space - \\space \\int \\space \\frac{sin \\space ^2 \\space x}{cos \\space x} \\space dx \\space + \\space C_1 \\space \\space \\\\\n \\space \\space \\space \\space = \\space - \\space \\int \\space \\frac{1-cos \\space ^2 \\space x}{cos \\space x} \\space dx \\space + \\space C_1 \\space \\space \\\\\n \\space \\space \\space \\space = \\space - \\space \\int \\space {(sec \\space x \\space - \\space cos \\space x)}dx \\space + \\space C_1 \\space \\space \\\\\nA= \\space - \\space [log \\space (sec \\space x \\space + \\space tan \\space x \\space )- \\space sin \\space x \\space ]+ \\space C_1 \\space \\\\\nB' \\space = \\space \\frac{y_1 \\space \\phi \\space (x)}{W} \\space \\\\\nB' \\space = \\space \\frac{cos \\space x \\space tan \\space x \\space }{1} \\space \\\\\nB'=sin \\space x \\space \\\\\nB= \\space \\int \\space sin \\space x \\space dx \\space + \\space C_2 \\space \\\\\nB= \\space -cos \\space x \\space + \\space C_2 \\space \\\\\nSubstitute \\space these \\space values \\space of \\space A \\space and \\space B \\space in \\space Eqn. \\space (1), \\space we \\space get\\\\\n \\space y \\space = \\space [\u2013 \\space log(secx \\space + \\space tanx) \\space + \\space sinx \\space + \\space \\space C_1] \\space cosx \\space + \\space [\u2013 \\space cos \\space x \\space + \\space \\space C_2] \\space sinx \\space \\\\\ny= \\space C_1cos \\space x \\space + \\space \\space C_2sin \\space x \\space \u2013 \\space cosx \\space log \\space (sec \\space x \\space + \\space tan \\space x) \\space \\\\\nThis \\space is \\space the \\space complete \\space solution. \\space \\space"
Comments
Leave a comment